Letter: fulminant‐onset complicated inflammatory bowel disease (IBD)—a unique subtype?. Issue 10 (24th April 2023) - Szigeti, Reka; Krishna, Mahesh; Kellermayer, Richard
LINKED CONTENT: This article is linked to Jayasooriya et al papers. To view these articles, visit https://doi.org/10.1111/apt.17370 and https://doi.org/10.1111/apt.17445